Green IT Model for Gulf Cooperation Council Organisations - Albahlal, Abdulaziz Ahmed (Curtin University, 2019)
This research aims to develop a Green IT model that suits the needs of the Gulf Cooperation Council (GCC) countries. A mix-methods approach that combines interviews with a survey was implemented to assess the model critically. The initial model developed for evaluating various Green models to assess the Governance, Social and Cultural, Information Technology and Green Management in GCC. The Green IT model aims to raise sustainability awareness in GCC countries based on their visions.